RISK FACTORS ASSESSMENT OF SUBACUTE RUMINAL ACIDOSIS IN CATTLE AND BUFFALOES IN SELECTED DISTRICTS OF PUNJAB, PAKISTAN - A. S. Chaudhry; M. H. Saleem M. A. Khan; M. S. Khan; K. Ashraf; I. Ahmad; K. Hameed (Journal of Animal and Plant Sciences, 2019)
Feeding of grain diets high in starch and low in fiber to increase intake of energy in the high yielding dairy cows usually result in subacute ruminal acidosis (SARA). The present study was designed to find out epidemiological risk factors associated with SARA in cattle and buffaloes in district Okara and Lahore of the Punjab, Pakistan. A total of 1226 dairy animals (cows =635 and buffaloes =591) suspected for SARA were screened. Animals showing signs of SARA were subjected to rumenocentesis and those with rumen pH of 5.1 to 5.7 were considered affected. The association of various risk factors with the disease was tested through Chi square test and later on quantified through generalized linear model. Results showed 16.32% prevalence in Okara compared with 10.78% in district Lahore. Significantly higher (p<0.05) prevalence was found in winter (15.51%), stall feeding (14.95%) and older animals (15.17%) in comparison with summer (11.41%), grazing (10.57%) and primiparous (7.96%) animals. Breed-wise comparison reveled significantly higher (p≤0.05) prevalence in Sahiwal cattle (23.61%) than Jersy (15.75%) or Friesian (15.38%), the difference between latter two breeds was non significant. Among buffalos, prevalence of SARA was lower (6.91%) in Nili Ravi compared non descript breed (8.79%), the difference was, however, non-significant. Various epidemiological factors: including species, area, age group, season, feeding pattern and lactation state were processed through generalized linear model. The species appeared to be the most significant factor, contributing maximum variation in disease with highest Odds, followed by lactating state, area, season, and age group.
Keywords: SARA; Ruminocentasis; Cows; Buffaloes; Okara; Lahore